Mr Uppity - Hargreaves, Roger (World International Ltd, 1972)
Mr. Uppity has quite a big head: He thinks he is better than everyone else and treats them accordingly. But one day he meets the King of the Goblins, who doesn't like Mr. Uppity's attitude. But what can he do to teach him a lesson?
Keywords: Juvenile literature-Fiction